How to Define the Content of a Job-Specific Worker's Health Surveillance for Hospital Physicians? - Martijn M. Ruitenburg; Monique H.W. Frings-Dresen; Judith K. Sluiter (Elsevier, 2016)
Background: A job-specific Worker's Health Surveillance (WHS) for hospital physicians is a preventive occupational health strategy aiming at early detection of their diminished work-related health in order to improve or maintain physician's health and quality of care. This study addresses what steps should be taken to determine the content of a job-specific WHS for hospital physicians and outlines that content. Methods: Based on four questions, decision trees were developed for physical and psychological job demands and for biological, chemical, and physical exposures to decide whether or not to include work-related health effects related to occupational exposures or aspects of health reflecting insufficient job requirements. Information was gathered locally through self-reporting and systematic observations at the workplace and from evidence in international publications. Results: Information from the decision trees on the prevalence and impact of the health- or work-functioning effect led to inclusion of occupational exposures (e.g., biological agents, emotionally demanding situations), job requirements (e.g., sufficient vision, judging ability), or health effects (e.g., depressive symptoms, neck complaints). Additionally, following the Dutch guideline for occupational physicians and based on specific job demands, screening for cardiovascular diseases, work ability, drug use, and alcohol consumption was included. Targeted interventions were selected when a health or work functioning problem existed and were chosen based on evidence for effectiveness. Conclusion: The process of developing a job-specific WHS for hospital physicians was described and the content presented, which might serve as an example for other jobs. Before implementation, it must first be tested for feasibility and acceptability.